Resistin Activates p65 Pathway and Reduces Glycogen Content through Keratin 8 - Fengyun Wen; Qiao Xia; Hui Zhang; Haipeng Shia; Amin Rajesh; Yanling Wu; Yi Yang; Zaiqing Yang (International Journal of Endocrinology)
Resistin is associated with metabolic syndrome and inflammatory conditions. Many studies have suggested that resistin inhibits the accumulation of glycogen; however, the exact mechanisms of resistin-induced decrease in glycogen content remain unclear. Keratin 8 is a typical epithelial intermediate filament protein, but numerous studies suggest a vital role of K8 in glucose metabolism. However, it is still not known whether K8 participates in the mediation of resistin-induced reduction of cellular glycogen accumulation. In this study, we found that resistin upregulated expression of the p65 subunit of NF-κB, which led to the promotion of K8 transcriptional expression; in turn, the expression of K8 inhibited glycogen accumulation in HepG2 cells.